2023
DOI: 10.3102/00346543231167795
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Game-Based Learning Interventions on Cognitive, Metacognitive, and Affective-Motivational Learning Outcomes in School: A Meta-Analysis

Abstract: Digital game-based learning (DGBL) interventions can be superior to traditional instruction methods for learning, but previous meta-analyses covered a huge period and included a variety of different target groups, limiting the results’ transfer on specific target groups. Therefore, the aim of this meta-analysis is a theory-based examination of DGBL interventions’ effects on different learning outcomes (cognitive, metacognitive, affective-motivational) in the school context, using studies published between 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 87 publications
0
9
0
4
Order By: Relevance
“…There is also a link between playing video games and cognitive skills. For example, puzzle games can increase cognitive skills such as problem-solving and fluid cognition (Akin, 2023;Barz et al, 2023;Cunningham & Green, 2023;Gray et al, 2019;Lamb et al, 2018;Rafiemanesh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a link between playing video games and cognitive skills. For example, puzzle games can increase cognitive skills such as problem-solving and fluid cognition (Akin, 2023;Barz et al, 2023;Cunningham & Green, 2023;Gray et al, 2019;Lamb et al, 2018;Rafiemanesh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gray et al (2019) reported that using BrainQuest, a mobile gaming experience combining physical activities, game design and cognitive challenges, improved executive functioning skills. Furthermore, Lamb et al (2018) and Barz et al (2023) identified a positive correlation between gaming and cognitive and affective outcomes related to the learning process.…”
Section: Motivations Of Playing Different Genres Of Gamesmentioning
confidence: 97%
“…Due to their capabilities in capturing and holding people's attention and in fostering sustained engagement and long-term loyalties, games have further become role models for engaging learners (Rigby, 2014) and citizens to solve complex scientific problems (Cooper et al, 2010;Spiers et al, 2023). Well-designed games can indeed promote both the required persistence in activities for practice and high quality of engagement that can foster deep human learning and problem solving (Barz et al, 2023;Hu et al, 2022;Ryan & Rigby, 2020). The extension of SDT (Ryan & Deci, 2000 based on research on video games (Ryan et al, 2006), technology design (Calvo & Peters, 2014), or digital learning (Sørebø et al, 2009) has shown in which ways psychological satisfactions for autonomy, competence, and relatedness can be evoked or undermined and thus affect players' intrinsic motivation and sustained engagement (Ryan & Rigby, 2020).…”
Section: Game-based Learning As a Way To Harness The Full Potential O...mentioning
confidence: 99%
“…As players interact with game systems, they can learn and then manipulate and act within them in ways that comply with ("win states") or reject ("lose states") its rules and norms (Gee, 2003). Evidence continues to grow for the positive impact of game-based learning across subject areas (Topping et al, 2022;Barz et al, 2023) including civics (LeCompte et al, 2011;Farber, 2021).…”
Section: Game-based Learningmentioning
confidence: 99%
“…iThrive Sim combines two evidence-based approaches: SEL programming (Durlak et al, 2011;Cipriano et al, 2023) and digital gameplay (Topping et al, 2022;Barz et al, 2023). The goal of this synergy is to capture and hold the interest of teens while offering transformational experiences that strengthen relationships in physical and virtual classrooms.…”
Section: Introductionmentioning
confidence: 99%